2017
DOI: 10.1161/circimaging.116.006308
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Arterial Load After Transcatheter Aortic Valve Replacement for Aortic Stenosis

Abstract: A ortic stenosis (AS) has been conceptualized as a mechanical problem (valve obstruction) requiring a mechanical solution (valve replacement).1 It is often considered to be a disease of fixed left ventricular (LV) afterload because of an obstructed valve, with the theoretical concern that a decrease in vascular resistance due to vasodilator therapy could cause severe hypotension without the ability to augment stroke volume due to fixed obstruction at the valve level.2 Several recent studies show, however, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 46 publications
(43 reference statements)
4
55
0
Order By: Relevance
“…The authors also noted the contradictory nature of an association between increased BP and improved outcomes, especially in elderly patients with the most arterial stiffness. In 2017, Lindman et al showed that higher systolic BP is associated with improved overall, but this study was limited to 1 year post-TAVR 18. In this study, we extended the period of HTN and outcome monitoring to better associate new onset or worsening HTN with improved outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…The authors also noted the contradictory nature of an association between increased BP and improved outcomes, especially in elderly patients with the most arterial stiffness. In 2017, Lindman et al showed that higher systolic BP is associated with improved overall, but this study was limited to 1 year post-TAVR 18. In this study, we extended the period of HTN and outcome monitoring to better associate new onset or worsening HTN with improved outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…However, in a recent published abstract by Alrifai et al pre-operative beta blocker use did not improve the overall mortality (3). Similarity, Lindman et al found no survival benefit at 1 year in patients after TAVR (4). In this trial, we aim to further characterize the impact of beta-adrenergic blockade on clinical outcomes following TAVR.…”
Section: Introductionmentioning
confidence: 57%
“…In this issue of Circulation: Cardiovascular Imaging, Lindman et al 8 explore the relationships among post-TAVR systolic blood pressure (SBP) and arterial load and survival in a cohort of 2141 prohibitive-or high-surgical risk patients enrolled in the PARTNER I trial (Placement of Aortic Transcatheter Valve; NCT 00530894) or continued access registry. Lower SBP (100-129 versus 130-170 mm Hg) and higher total and pulsatile (but not resistive) arterial load were associated with an increased 30-day to 1-year all-cause mortality.…”
Section: See Article By Lindman Et Almentioning
confidence: 99%
“…Lindman et al 8 have redrawn the clinician's attention to the evaluation and management of blood pressure in elderly, prohibitive-, or high-surgical risk patients after TAVR. Their findings suggest that lower SBP may be a marker for reduced survival in this cohort and may best be avoided if possible and as circumstances and drug choices allow.…”
Section: See Article By Lindman Et Almentioning
confidence: 99%
See 1 more Smart Citation